Liquiritin ameliorates painful diabetic neuropathy in SD rats by inhibiting NLRP3-MMP-9-mediated reversal of aquaporin-4 polarity in the glymphatic system - Jia, Shuai-Ying; Yin, Wen-Qin; Xu, Wen-Mei; Li, Jiang; Yan, Wei; Lin, Jing-Yan (Frontiers in Pharmacology, 2024)
Despite advancements in diabetes treatment, the management of Painful Diabetic Neuropathy (PDN) remains challenging. Our previous research indicated a significant correlation between the expression and distribution of Aquaporin-4 (AQP4) in the spinal glymphatic system and PDN. However, the potential role and mechanism of liquiritin in PDN treatment remain uncertain. This study established a rat model of PDN using a combination of low-dose Streptozotocin (STZ) and a high-fat, high-sugar diet. Rats were treated with liquiritin and MCC950 (an NLRP3 inhibitor). We monitored fasting blood glucose, body weight, and mechanical allodynia periodically. The glymphatic system's clearance function was evaluated using Magnetic Resonance Imaging (MRI), and changes in proteins including NLRP3, MMP-9, and AQP4 were detected through immunofluorescence and Western blot techniques. The results indicate that after treatment, PDN rats showed improvements in all measured parameters. Consequently, liquiritin may alleviate PDN by modulating AQP4 expression through the NLRP3-MMP-9 pathway.